Health practices resulting from risk factors for breast cancer in working women - Andrea Gomes Linard; Raimunda Magalhães da Silva; Francisco Antonio da Cruz Mendonça (Rev Rene)
Breast cancer is characterized as a public health problem. This study intended to verify the risk factors for breast cancer with employees from a university in Ceara and its relations with the health practices developed by such women. It was a transversal research, carried out from the period of January through April 2006, with 200 employees from a private university in Fortaleza. Data were collected with a questionnaire, organized at the SPSS and grouped in accordance with pre-established variables, using the risk factors in accordance with the INCA. The results indicated that 78, 9% were taking contraceptive pills; 62, 6% reported to be using alcoholic beverages; 21, 0% late menopause; 18,8% were smoking 18,5% had precocious menarche. About health practices 78, 8% carried out the breast self-examination. It was concluded that the women are attempted to the risk factors and adopt in their life style some health practices directed to precocious detection of the breast cancer.